Did the U.S. Carry Out a Ukrainian Coup? - The Real News Network (2014)
Investigative journalist Robert Parry talks about Russia's move to invade Ukraine's Crimean peninusla and the role of the US and the west in fomenting crisis there See more videos: http://therealnews.com
Keywords: robert parry; ukraine